THE DISTRIBUTION OF RECENT BENTHIC FORAMINIFERA IN THE ARAFURA SEA - Suhartati M. Natsir; Rubiman Rubiman (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2010)
Arafura Sea consists of shallow waters and located in the Southern of Papua to the north coast of Australia. The waters is vegetated by shallow-water ecosytems such as mangrove, seagrass bed, and coral reefs. The Arafura continental shelf is predominated by sediment from late Paleozoic, Mesozoic to Cenozoic and underlain by granitic basement. Foraminifera is a single cell microorgainsm, has pseudopodia with high level of diversity. Foraminifera dwells in every level of sea depth, from estuary to the deep sea. However, a certain species commonly dwells in the specific profundity. The aim of the study was to recognize the distribution of benthic foraminifera in the waters of Arafura Sea and it relation with the environmental characteristics. As many as 11 sediment samples was collected in May 2010 from the water of Arafura Sea using a box core with capcity of 0,3 m3. Laboratory analyses on the colleted samples were performed to determine the type of sediments and identify the benthic foraminifera, and to determine the abundance of each samples. The number of species found from the collected sediments were 37 species consisting of 29 genera of which most of them were member of Suborder Rotaliina and many of them belong to Suborder Miliolina and Textulariina. The most common species of the sampling sites were Ammonia beccarii and Pseudorotalia schroeteriana. The Arafura Sea commonly recognized as shallow waters, open seas, with current speed of midium to high. The predominant sediment type of the waters is sandy mud and little of clay.Keywords: distribution, benthic foraminifera, sediment and Arafura